A REVIEW FOR THE COORDINATION COMPOUNDS IN THE HUMAN BODY AND SOME OF ITS CLINICAL AND BIOLOGICAL ASPECTS - Ghufran Sh. Al-Obaidy; Ghufran Sh. Al Obaidy (Scholar Express Journals, 2022)
In the past two decades, studies in the lab (using animals) and in the clinic have demonstrated that numerous pathologic conditions of the body are accompanied by statistically significant changes in the body's cellular and systemic metal metabolism. Anomalies in metal metabolism can be the cause of any chronic disease for which the cause has not yet been determined. Throughout the history of human medicine, coordination compounds based on metals have been utilized to treat a variety of illnesses, including cancer. There have been several metal coordination complexes developed, including those made of Pt, Ru, Au, or Cu, produced, and tested since the discovery of cisplatin in 1965 in an effort to create therapeutically effective and secure medications. When discussing the usage of cytostatic metal complexes, many articles now highlight the most successful examples of pt- and non-pt-based drugs in preclinical and clinical trials. In this review, we aim to provide an overview of coordination compounds and to examine the chemical and biological properties of coordination compounds based on metals. We'll also give a brief description of how these compounds were designed and why they were made, as well as a summary of the physicochemical and biochemical characteristics of metal complexes
Keywords: Hemoglobin; coordination compounds; Zinc- finger protein; Vitamin B12